South African Higher Education: Transformation or/and Decolonisation? - Luqman Muraina; Yonela Toshe-Mlambo; Siviwe Cingo (University of Johannesburg, 2024)
Transformation is the christened name of institutional activities seeking to change South Africa 'into the opposite of apartheid', including in higher education (HE). However, transformation failures meant that students at universities in South Africa, through several #MustFall movements, protested around their misgivings about 'transformation' and advocated for a decolonial turn. Decolonisation, therefore, has become the preferred name for change to some sections of HE, thereby creating a conflict with 'transformation'. Our study collected responses on the meaning of transformation and decolonisation and their capability to change the hegemonic structure and Western institutional culture in universities. The qualitative study was anchored in Fomunyam's social transformation theory and used semi-structured interviews to collect data from 11 participants from a South African university. They were analysed thematically (reflexively). Findings depicted opinions favouring both transformation and decolonisation to achieve changes required in HE. The liberal and linguistic nature of transformation means it can be manipulated for different agendas and research purposes. Meanwhile, decolonisation, anchored in histories of Africa's oppression, is specific about recentring Africa in the universities. In conclusion, it is vital to exercise caution to avoid 'decolonial fatigue' which would make decolonisation a rhetoric just like transformation.